Validated Spectrophotometric Methods for Simultaneous Determination of Food Colorants and Sweeteners - Fatma Turak; Mahmure Ustun Ozgur (Journal of Chemistry)
Two simple spectrophotometric methods have been proposed for simultaneous determination of two colorants (Indigotin and Brilliant Blue) and two sweeteners (Acesulfame-K and Aspartame) in synthetic mixtures and chewing gums without any prior separation or purification. The first method, derivative spectrophotometry (ZCDS), is based on recording the first derivative curves (for Indigotin, Brillant Blue, and Acesulfame-K) and third-derivative curve (for Aspartame) and determining each component using the zero-crossing technique. The other method, ratio derivative spectrophotometry (RDS), depends on application ratio spectra of first- and third-derivative spectrophotometry to resolve the interference due to spectral overlapping. Both colorants and sweeteners showed good linearity, with regression coefficients of 0.9992–0.9999. The LOD and LOQ values ranged from 0.05 to 0.33 μgmL−1 and from 0.06 to 0.47 μgmL−1, respectively. The intraday and interday precision tests produced good RSD% values (<0.81%); recoveries ranged from 99.78% to 100.67% for all two methods. The accuracy and precision of the methods have been determined, and the methods have been validated by analyzing synthetic mixtures containing colorants and sweeteners. Two methods were applied for the above combination, and satisfactory results were obtained. The results obtained by applying the ZCDS method were statistically compared with those obtained by the RDS method.